The Role Of Strategic Management In Strengthening Students' Character And Digital Literacy - Widayati, Puji Nurwidayati; Ratna Purwanti; Ahmad Suriansyah (Jurnal Inspirasi Pendidikan, 2025)
Abstract: Twenty-first-century education requires educational institutions to focus not only on academic achievement but also on character development and the enhancement of students' digital literacy. This study aims to analyze the role of strategic management in systematically and sustainably integrating these two crucial aspects within the environment of State Vocational High School 1 Kapuas Murung. The author employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and document analysis. The findings indicate that strategic management at the school is implemented through vision-based program planning, the synergistic execution of character and digital learning activities, and periodic program evaluation. These strategies foster a school culture that supports the development of students who are not only technically proficient but also possess integrity, digital ethics, and critical thinking skills. This study recommends strengthening school managerial capacities in formulating and implementing integrated policies on character education and digital literacy.